Why DDT is the only way to explain some vapor cloud explosions. Issue 3 (24th February 2017) - Johnson, D.M.; Tam, V.H.Y.
Abstract : The possibility that Deflagration to Detonation Transition (DDT) occurs in vapor cloud explosions (VCEs) in industrial accidents has generally only been recognized for very reactive fuels such as hydrogen and ethylene. Assessment of the explosion hazards and risks associated with less reactive fuels such as propane and other alkanes has generally been based around the assumption that, in practice, only a deflagration can occur. This has the benefit that the magnitude of the maximum hazard to surrounding areas is defined by the physical parameters of any congested process region and not by the extent of the vapor cloud, as would be the case if there was a sustained detonation. However, following the Buncefield incident in the UK in 2005, a considerable amount of effort was expended in explaining the major VCE that occurred. This initially involved gathering and interpreting the evidence from the incident but then extended to experimental and theoretical research over two phases and lasting five years. Further research since showed that DDT can be achieved within dense vegetation and regions of pipework with a relatively small extent (of the order of a few meters). The results from this project will be summarized, indicating why the only explanation that is consistent with all of the evidence is a DDT soon after ignition of the cloud, with a sustained detonation then propagating through the majority of the cloud. Reference will be made to other incidents where similar evidence was observed. Awareness of the significance of such evidence will be important in the investigation of future VCEs. In addition, the possibility of DDT needs to be recognized in the methodologies used to assess VCE hazards. © 2017 American Institute of Chemical Engineers Process Saf Prog 36: 292–300, 2017